Observing the Music Teaching By Using “Carl Orff Method in Mojiang Middle School, Guangdong Province, The People’s Repiblic of China - Ruoling, Liu; Yodwised, Chutasiri; Sin Mei, Lim (Journal of Roi Kaensarn Academi, 2024)
As one of the three major music education systems in the world, the Orff music teaching method was developed by the German music educator and composer Carl. Orff was founded in 1924. This research aims to observe music teaching by using Carl Orff method in Mojiang Middle School. Observation and interview methods were used in this study. First, the researchers observed the use of Carl Orff pedagogy by music teachers in three classes of 150 students in Mojiang Middle School, summarized the teaching methods used by teachers in the classroom, and observed and summarized the reactions and situations of students. Secondly, the researcher interviewed the music teachers of three classes in Mojiang Middle School to find out whether the three classes were taught by Carl Orff teaching method and the teachers’ opinions. The result shows that Carl Orff teaching method is suitable for the third-grade music course in Mojiang Middle School. Through observing the state and reaction of the students in the three classes, and interviewing the music teachers of the three classes, the results show that the Carl Orff teaching method is suitable for the music class of the third grade in Mojiang Middle School.